2019
DOI: 10.3390/ijms20215356
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 Inhibits Apoptosis of Porcine Primary Granulosa Cell by Targeting Degradation of BimEL

Abstract: Insulin-like growth factor-1 (IGF-1) is an intra-ovarian growth factor that plays important endocrine or paracrine roles during ovarian development. IGF-1 affects ovarian function and female fertility through reducing apoptosis of granulosa cells, yet the underlying mechanism remains poorly characterized. Here, we aimed to address these knowledge gaps using porcine primary granulosa cells and examining the anti-apoptotic mechanisms of IGF-1. IGF-1 prevented the granulosa cell from apoptosis, as shown by TUNEL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 62 publications
3
12
0
Order By: Relevance
“…The LC3-II/LC3-I ratio was also increased in the chloroquine group compared with the control ( Figure S7 B). This is consistent with previous studies showing that LC3-II, a substitute of autophagic degradation, was increased relative to LC3-I when autophagic degradation was inhibited by the lysosome inhibitor chloroquine ( Han et al., 2019 ).…”
Section: Resultssupporting
confidence: 93%
“…The LC3-II/LC3-I ratio was also increased in the chloroquine group compared with the control ( Figure S7 B). This is consistent with previous studies showing that LC3-II, a substitute of autophagic degradation, was increased relative to LC3-I when autophagic degradation was inhibited by the lysosome inhibitor chloroquine ( Han et al., 2019 ).…”
Section: Resultssupporting
confidence: 93%
“…IGF1 is a growth‐related factor of granulosa cells, and it has been reported to constrain granulosa cell apoptosis through regulating expression of BCL‐2‐interacting mediator of cell death (Bim) 17 . Our study firstly confirmed that IGF1 acted as a target of kurarinone, and kurarinone upregulated IGF1 expression in H 2 O 2 ‐treated KGN cells.…”
Section: Discussionsupporting
confidence: 69%
“…There were 8 overlapping targets (HRAS, FGFR2, PPARG, FGFR1, LGALS3, IGF1, ST14 and AKT1) by matching the two groups of targets (Figure 4A). Among these targets, IGF1 was the only one that has been reported to be associated with granulosa cell function 17 . Moreover, IGF1 functions as one important upstream of the PI3K/Akt signaling 30–32 .…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy can clear aggregated misfolding proteins by inducing the expression of autophagy-related proteins including Beclin1, p62, and LC3. IGF-1 induces autophagy by upregulating the Beclin1 and LC3-II levels [ 64 ]. Wen et al reported that the intramuscular injection of human IGF-1 with a self-complementary adeno-associated virus vector in the cells and mouse models of ALS could upregulate mitochondrial autophagy and suppress mitochondrial apoptosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%